'All that jazz': the relationship between music festival visitors' motives and behavioural intentions. Issue 19 (26th November 2019) - Kruger, Martinette; Saayman, Melville
ABSTRACT: This exploratory study investigated the relationship between visitors' behavioural intentions (ex-post) and their motives (ex-ante) for attending a jazz festival. The aim was to discover whether a music festival brings additional intangible benefits. The research followed a quantitative approach by conducting a visitor survey at the Cape Town International Jazz Festival in South Africa. Structural Equation Modelling showed that music festivals have the potential to create benefits beyond the festival itself or the host destination, particularly fostering an appreciation of a music genre, increasing purchasing of music, and boosting music tourism. The findings showed that a music festival could have far-reaching benefits that can contribute to its legacy. It also showed that visitors' motives have a unique relationship with their behavioural intentions, which emphasizes the need to market the festival accordingly.